UJI AKTIVITAS EKSTRAK BUAS-BUAS (PREMNA SERRATIFOLIA LINN) SEBAGAI ANTI KOLESTEROL SECARA IN VITRO - Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTPremna Serratifolia Linn is believed to reduce cholesterol and as an alternative herbal medicine solution among the cost of medicine and the side effects caused by synthetic drugs. This study was conducted in several phases by using Premna Serratifolia Linn which was drained, mashed, and macerated using ethanol, choloform, and n-heksane. Extract obtained from evaporation, then whighed, and stored in a desiccators. Anti-cholesterol activity was tested test by using in vitro : began with determination of the maximum wavelength of the cholesterol standard solution with a UV-Vis spectrophotometer and continued by manufacturing the standard curve with the cholesterol concentration of 0.5; 0.75; 1; 1.25; and 1.5 mL and 1000 ppm cholesterol solution. Furthermore, maximum absorbance wavelength was measured in order to obtain the maximum wavelength of the cholesterol. The study reveled that the solvent extraction of ethanol produced the largest  rendement. The extract Premna Serratifolia Linn is functioned as an anti-cholesterol. In addition,  the absorbed reduction of 100 ppm cholesterol standard solution found in the addition of 0.5 mL choloform extract.Keywords: Anti-cholesterol, Premna Serratifolia Linn, In Vitro